2006
DOI: 10.1007/s10479-006-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization problems in electron microscopy of single particles

Abstract: Electron Microscopy is a valuable tool for the elucidation of the three-dimensional structure of macromolecular complexes. Knowledge about the macromolecular structure provides important information about its function and how it is carried out. This work addresses the issue of three-dimensional reconstruction of biological macromolecules from electron microscopy images. In particular, it focuses on a methodology known as "single-particles" and makes a thorough review of all those steps that can be expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The initially unknown parameters t i and r i in Eq. (1) are often referred to as 'hidden variables' (Sorzano et al, 2006). The best estimate of A can be calculated by optimizing S, which requires determination of the hidden parameters h -a process known as alignment.…”
Section: Subtomogram Alignment By Quasi-expectation Maximizationmentioning
confidence: 99%
“…The initially unknown parameters t i and r i in Eq. (1) are often referred to as 'hidden variables' (Sorzano et al, 2006). The best estimate of A can be calculated by optimizing S, which requires determination of the hidden parameters h -a process known as alignment.…”
Section: Subtomogram Alignment By Quasi-expectation Maximizationmentioning
confidence: 99%
“…Yet the importance of a robust first estimation cannot be overstated. Several works have indeed demonstrated that the nature of this initial structure can considerably affect the final reconstruction ( Henderson et al, 2012 , Sorzano et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of heavy noise on nearly identical projections, their low contrast, the conformational heterogeneity of molecular complexes, the unknown projection directions, the finite number of measurements, and the incomplete knowledge of the imaging process all cause the determination of the 3D structure to be a highly ill-posed inverse problem that may also suffer from overfitting. Moreover, the convergence of the global process depends heavily on the quality of the initial reconstruction ( Sorzano et al, 2006 , Henderson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The whole 3D reconstruction process is commonly managed starting with an initial model estimation, which can be seen as an estimation of the start-ing point in the solution landscape, followed by a refinement to move along the whole landscape, improving the reconstructed model in every step. The refinement algorithms easily get stuck in local minima of the solution landscape [90]. Therefore, a good design of the initial volume estimation and refinement algorithms is key in the accuracy of the final 3D model generated.…”
Section: D Analysismentioning
confidence: 99%